Is muscle stiffness a determinant for range of motion in the leg muscles? - Reiner, Marina M.; Tilp, Markus; Nakamura, Masatoshi; Konrad, Andreas (Biology of Sport, 2024)
Previous training studies with comprehensive stretching durations have reported that an increase in range of motion (ROM) can be related to decreases in muscle stiffness. Therefore, the purpose of this study was to analyze the association between the passive muscle stiffness of three muscle groups (triceps surae, quadriceps, hamstrings) to the respective joint ROM. Thirty-six healthy male soccer players volunteered in this study. After a standardized warm-up, the muscle stiffness was tested via shear wave elastography in six muscles (gastrocnemius medialis and lateralis, rectus femoris, semitendinosus, semimembranosus, and biceps femoris long head). The hip extension, hip flexion, and ankle dorsiflexion ROM were also assessed with a modified Thomas test, a sit and reach test, and a standing wall push test, respectively. We found significant moderate to large correlations between hip flexion ROM and muscle stiffness for the semimembranosus (rP = –0.43; P = 0.01), biceps femoris long head (rP = –0.45; P = 0.01), and overall hamstring stiffness (rP = 0.50; P < 0.01). No significant correlations were found for triceps surae (rP = –0.12; P = 0.51 to 0.67) and rectus femoris muscle stiffness (rP = 0.25; P = 0.14) with ankle dorsiflexion and hip extension ROM, respectively. We conclude that muscle stiffness is an important contributor to hip flexion ROM, but less important for hip extension or ankle joint ROM. Additional contributors to ROM might be tendon stiffness or stretch/pain tolerance.